Analysis of the Interrelations among Shift Work, Job Stress, Job Satisfaction and Health: a Petrochemical Complex Case Study - Hanieh Nikoomaram (International Journal of Occupational Hygiene, 2019)
This study was aimed to investigate the interrelations among shift work, job stress, job satisfaction, and health at Shazand Petrochemical Company in Iran. The current research was carried out in two phases. The influencing and influenced variables and specified their priorities as per level of influence were identified in the first phase. An integrated Fuzzy-DEMATEL method was applied to analyze this study. A multiple regression method was used to determine the significance of the variables in the second phase. The results of this study indicated that the shift work was the most effective variable in health. Whereas, job satisfaction and job stress were in the second and third places, respectively. The multiple regression analysis was confirmed that the results of the fuzzy-DEMATEL regarding shift work, job stress, and job satisfaction significantly affect employees’ health. It can be concluded that shift working, where night shifts included, would have negative impact on health. This finding emphasized the importance of shift work as a major challenge in industrial workplaces.